Dynamics Superior Dairy Cow Compost Enriched with Inorganics Fertilizer on Yields and Nutritive Values of Pennisetum Grass Cultivars - Hidayat, Nur; Hendarto, Eko; Haryoko, Imbang; Harwanto; Prasetyo (ANIMAL PRODUCTION, 2023)
Fertilization step is the main strategy in producing good plants. Dairy cow dung as a renewable natural resource is abundant and can be a source of additional income for farmers if it becomes superior compost. Through the enrichment of various types and doses of inorganic fertilizers, it is expected to have economic value, especially for feed crops. The aim of the study was to obtain a superior compost formula for dairy cow dung enriched with various types and doses of inorganic fertilizers on the production and nutritional value of pennisetum grass. Using a nested design with the main treatment of 3 types of pennisetum grass (King, Gajah and Odot), the treatment children were enrichment of 3 inorganic fertilizers (Urea, NPK and ZA) with 3 doses (equivalent to 100, 200 and 300 kg urea per hectare per defoliation) with 3 repetitions. The study was conducted on plots measuring 1 x 1 square meter at the third defoliation growth. Parameters observed were fresh forage production and nutritional quality (crude protein, crude fiber and crude fat content). The data obtained were analyzed based on Nested Design, BNJ and regression. The results showed that dairy cow dung can be made into superior compost, enriched with 300 kg of NPK and ZA fertilizers equivalent to urea fertilizer and has provided fresh forage production and good nutritional quality on all Pennisetum grasses.